2008
DOI: 10.1007/s11242-008-9309-6
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection Boundary-Layer Flow Near the Stagnation Point on a Vertical Surface in a Porous Medium: Brinkman Model with Slip

Abstract: The steady boundary-layer flow near the stagnation point on an impermeable vertical surface with slip that is embedded in a fluid-saturated porous medium is investigated. Using appropriate similarity variables, the governing system of partial differential equations is transformed into a system of ordinary differential equations. This system is then solved numerically. The features of the flow and the heat transfer characteristics for different values of the governing parameters, namely, the Darcy-Brinkman, , m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
300
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 604 publications
(324 citation statements)
references
References 20 publications
5
300
0
Order By: Relevance
“…Harris et al [22] built a similarity solution for the boundary layer developed near the stagnation point on a porous plate positioned vertically. A numerical work on mixed convection in jet impingement on a flat porous plate revealed that increasing the jet width and the Reynolds number lead to the magnification of the average Nusselt number [23].…”
Section: Introductionmentioning
confidence: 99%
“…Harris et al [22] built a similarity solution for the boundary layer developed near the stagnation point on a porous plate positioned vertically. A numerical work on mixed convection in jet impingement on a flat porous plate revealed that increasing the jet width and the Reynolds number lead to the magnification of the average Nusselt number [23].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the nanofluids with higher thermal conductivity widens the range of for which the solution exists. There are several studies reported the existence of dual solutions for the similar problem such as Merkin [16], Weidman et al [17], Paullet and Weidman [18], Harris et al [19] and Postelnicu and Pop [20]. They indicated that the first solution is stable and physically relevant unlike those of the second solutions.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, if an initial decomposition, then the flow is declared as stable when the smallest eigenvalue is a positive value. As it has been recommended by Harris et al [20], as a result of relaxing a boundary condition on 0 ( ) …”
Section: Solutions Of Stabilitymentioning
confidence: 99%